A method for evaluation reliability of system - Pho, Nguyen Van; Chinh, Nguyen Xuan (Vietnam Journal of Mechanics, 1996)
In this paper, the authors have presented a method for evaluation reliability of system. The method includes three steps: - Deterministic calculation by finite element method to find inner forces of structure. In which aloes of design parameters and loads are chosen as their expectations. - To find reliability of every element according to statistic data’s of design parameters and sternal loads. In which inner forces of structure are external force of element. - To evaluate reliability of system by to determine lower and upper bounds. For illustration, evaluation of reliability of multi-story frame of reinforce concrete is considered.